Study on the effects of varying concentrations of xylitol on the weight, and blood glucose, and cholesterol levels of Mus musculus L. (ICR mice) - Sy, Irben Jeremy Y. (Animo Repository, 2018)
Background: High sugar intake has increased the risk of having diabetes and cardiovascular diseases. Many sugar substitutes have surfaced to combat these problems; however, there is risk associated with increased frequency of intake. Aims and Objectives: With the known effects of frequent sugar intake, varying concentrations of the sugar substitute, and xylitol were used to determine its effects on the weight, blood glucose, and blood cholesterol levels on ICR mice. Materials and Methods: In this study, 25 mice were used as subjects that were split into five groups randomly: Group 1 (negative control) was not given any treatment, Group 2 (positive control) was given 10% sucrose solution, and Groups 3–5 (treatment groups) were given 10%, 15%, and 20% xylitol solutions, respectively. Before the treatments were given, baseline levels were determined for glucose and cholesterol using glucose cholesterol uric acid Easy Touch® multifunction monitoring system, and an analytical balance for the weight. The tests were determined again after giving the treatments to the groups for 3 weeks. The results of these tests after treatment were then compared with the baseline. Results: Results showed that the change in weight and change in blood cholesterol level in xylitol-treated groups were not significantly different with the positive control, while the change in blood glucose level showed that xylitol-treated groups were significantly different with the positive control. It was also shown that the tests done in varying concentrations of xylitol did not differ from each other. Conclusion: This shows that xylitol does not greatly affect the blood glucose level, but is shown to have the same effects with sucrose on the weight and blood cholesterol level.